Wasteful or sensible? Donor imageries in İstanbul's food banks. (May 2020) - Türkkan, Candan
Abstract: This paper explores how the staff of İstanbul's food banks perceive the donors and the donations. The paper begins by exploring the literature on food banks; what food banks recover and redistribute; and the role food banks play in managing food insecurity. Next, how these three issues are represented in different models of food banks are discussed: in the non-profit model, the donors are "socially aware citizens" who contribute to the common good by helping to feed the hungry; whereas, for the for-profit model they are "caring capitalists" doing their best to reduce their carbon footprint and eliminate food waste while effectively managing the costs of waste disposal. In the municipal social markets, in contrast, the donors are "prodigal consumers" who cannot make correct resource allocation decisions and waste food as a result. For all the models, the donors are predominantly individuals or households and waste generation is perceived as a consumer problem, whereas in practice the donors are mostly corporations giving away their surplus stock. The paper concludes by underlining that this misperception shifts the conversation on waste generation and management away from production and supply chain problems and disciplines individuals as consumers.